Effect of semi-setting position on post-dural puncture headache in women with elective cesarean section - Saeed Khorramnia; Reza Nejadhasan; Fateme Rajaeipoor; Zahra Asadollahi (Majallah-i Zanān, Māmā̓ī va Nāzā̓ī-i Īrān, 2019)
Introduction: Headache is one of the complications of spinal anesthesia in various surgeries. Spinal anesthesia has a major role in cesarean section. This study was performed with aim to investigate the effect of semi-sitting position on headache after spinal anesthesia in women undergoing elective Cesarean Section. Methods: This interventional study was performed on 110 pregnant women with cesarean section at Rafsanjan Nikanfas Hospital in 2018. In recovery time, the subjects were placed into two groups: head position in 30 degree and flat position. The incidence and intensity of headache was assessed using the pain Visual Analogue Scale in the first, second and third days after the surgery. Data were analyzed by SPSS software (version 18) and independent t-test, Chi-square test and Two-way Repeated Measures ANOVA. PResults: Mean of headache severity in the group with flat head position in the first, second and third days was 0.98 ± 2.41, 0.87 ± 2.16 and 0.78 ± 1.92, respectively, and in the group of 30 degrees head position was 1.41 ± 2.89, 1.30 ± 2.70 and 1.12 ± 2.33, respectively. The severity of pain in both groups was significantly decreased on different days (p <0.0001), although there was no significant difference between the two groups (p =.379). Conclusion: Flat head positioning during recovery of spinal anesthesia in women undergoing elective cesarean section decreased the severity of postoperative headache compared with head position at 30 degrees, although this difference was not statistically significant.